A study on the Relationship Between Employee Satisfaction and Employees’ Performance - Ranga, Ashish; Kamboj, Reshma (Institut Pariwisata Trisakti, 2018)
A performance appraisal (PA), to boot ascertained as a performance review, performance analysis, (career) development discussion, or employee appraisal is also a way by that the work performance of an associate employee is documented and evaluated. The Performance appraisal has been viewed by lecturers and human resource practitioners as a significant human resource management practices as a result of it yields selections that area unit crucial and integral to varied human resource actions and outcomes. Yet, an honest Performance appraisal system remains a smart challenge for managers and employees thanks to psychological feature, psychological feature and behavioral factors associated with it. Employee outcomes among the sort of labor performance, effective structure commitment and turnover intention area unit is undeniably variety of the foremost necessary issues during a corporation.The management has to be compelled to concentrate to the extent of satisfaction in performance appraisal to substantiate that employees are happy and contribute utterly to their organization throughout the tenure of their employment with the organization. This can be often very crucial to support the expansion of an organization. The aim of this paper is to specialize in the impact of performance appraisal on employee's performance and to boot trace impact of motivation issue, as a result of it affects the association of performance appraisal and employee's performance.The paper reviews the• The relationship between perceptions of performance appraisal fairness and employee engagement in the context of the business organization.• The reaction of employees to these performance assessments.